Videographic Study and Objective Classification of Gait in Patients with Neurological Diseases - Díaz Novo, Carlos; Montoya Pedrón, Arquímedes; Zamora Matamoro, Larisa; Cuadra Sanz, Manuel Bárbaro; Molina Mojica, Ángel Valentín (TECCIENCIA, 2019)
Using videography, a cross-sectional descriptive-multivariate study was carried out, consisting of 61 patients with clinical, neurological and genetic diagnosis of Spinocerebellar Ataxia (SCA) and Cerebrovascular Accidents (CVA), as well as 51 healthy individuals chosen at random, attended in the Neurology consultation of the General Teaching Hospital Dr. Juan Bruno Zayas Alfonso in Santiago de Cuba. The results of the metrological evaluations performed on the instrumental proposal are included in the work, and the behavior of the kinematic variables (gait speed, excessive increase in step width and lateral oscillations of the hip) are analyzed, for 3 manifestations of the movement of the groups of healthy and sick subjects. Finally, the discriminant linear models obtained for different groups of healthy and sick subjects whose validation reveals their potential usefulness for the study of normal and pathological movement are included.